The Role of Artificial Intelligence in Transforming News Production at Liputan6.com - Rosadi, Dian; Fadilah, Efi; Puspitasari, Lilis (Jurnal Kajian Jurnalisme, 2026)
Background: AI technology is one of the innovations currently receiving the most attention in the media industry. The integration of AI into online journalism has emerged as a transformative force. Purpose: This study aims to analyze of AI in digital journalism practices at the online media Liputan6.com. It also aims to identify the changes in news production that have occurred since the advent of AI, as well as the opportunities and challenges associated with the use of AI in the news production process at online media. Methods: The method used in this study is qualitative, employing a case study design. The case study method was chosen because the object of this study is a single media organization, namely Liputan6.com. There are three key informants who serve as the subjects of the study. These informants were selected through purposive sampling. Results: The findings of this study indicate that the Liputan6.com editorial team uses AI for three main functions. First, as a tool to assist in news content production. Second, to monitor topics or issues currently being discussed by the public and their distribution. Third, as technological infrastructure within an integrated workflow. Main transformation that has taken place lies not in a change in journalistic principles, but rather in changes to the workflow and efficiency of news production. Conclusion: The entire process of validation, verification, and editorial decision making remains entirely in the hands of journalists. This further underscores that AI’s role at Liputan6.com is that of a supporting tool or assistant, not a replacement for journalistic work. Implications: Theoretically, these findings strengthen the argument of the theory of technological determinism that the presence of AI technology transforms workflows in newsrooms. Practically, these research findings encourage media organizations to develop internal policies on AI, journalism education institutions to integrate AI literacy into their curriculum, and policymakers to formulate adaptive regulations.